Republic of San Marino : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper describes the developments and challenges in the financial sector of the Republic of San Marino. The study analyzes the structure of the financial sector, compares the performance of Sammarinese banks with those in other countries, reviews the legal and regulatory environment as well as supervisory practices, and discusses the challenges facing the banking system. The paper also provides the statistical appendix report for the country.